(untitled) (Journal on studies and research of academic knowledge, 2017)
The general objective of this research was the development of a monitoring device for motorcycle traffic accidents for the quick assistance of victims. It started from the theoretical basis of the victims of the types of provocative traumas in a mishap on a motorcycle, have great chances of being saved or death, if they are treated in the first hour after the accident. This time interval is called the golden hour. The research was quantitative and applied. The variables given in a collision or fall were determined, which are mainly the impact and the loss of the balance of the mobile. To know the moment of the collision, we chose inertial type impact sensors, simulators by pulses in / out and to measure the inclination the accelerator / gyroscope mpu6050 was chosen. The control was made with Arduino Mega, the reception of the satellite coordinates was by means of the new one and the sending of the coordinates was made possible via SMS with the GSM module A6. Individual tests were carried out for each module separately in the laboratory and with the final prototype in open air areas. The message of the location area of the perimeter was successfully sent, indicating the functionality of the prototype. The prototype has a reduced size so it has the potential of application to commercial motorcycles.